EMPLOYING THE VALUE STREAM MAPPING BY USING THE PROCESS ACTIVITY MAPPING TO IMPROVE THE EFFICIENCY OF THE MEDICAL SERVICE - Ahmed Hameed Eesa; Saeed Hamad Eslaim (American Journals, 2024)
This study sought to employ the value Stream mapping by using the process activity mapping as one of its tools in redesigning the medical service in order to increase its efficiency. By getting rid of the waste that makes the waiting time for the patient longer at a time when he is in dire need of the necessary health care, with the shortest possible waiting period. The problem of the study is represented in the large number and length of the approved procedures for treating the patients, which led to an increase in waiting times, which negatively affected the value of the service provided to the customer. The study derived its importance as it deals with one of the most vital sectors, and an attempt to arouse the interest of health organizations. The study followed the method of a case study, in its applied side, it relied on analyzing current value Stream mapping through the use of one of its tools (process activity mapping) in order to identify waste, eliminate it or reduce it, and identify potential improvement areas, thus contributing to achieving the requirements of agility in work to improve the efficiency of service provided to customers. The study reached a set of conclusions, the most important of which are: "Long waiting times and low service efficiency indicators for the case of the research sample, the lack of effective maintenance and repair systems to qualify important and expensive devices, in addition to their great importance in facilitating tasks and reducing waiting time".
Keywords: Value Stream Mapping, Operation activity mapping, service efficiency.